Effect of Rehabilitation Training Based on Automatic Extraction Algorithm on Knee Anterior Cruciate Ligament Injury Caused by Exercise. (2nd May 2022) - Zhu, Sibo; Gao, Jie
Abstract : Objective . In order to explore the effect of rehabilitation training based on automatic extraction algorithm on knee anterior cruciate ligament reconstruction under arthroscopy. Methods . 81 patients with anterior cruciate ligament injury were randomly divided into observation group (42 cases) and control group (39 cases). The control group was given routine nursing, while the observation group was given rehabilitation training guidance based on automatic extraction algorithm. Lysholm score, HSS score, and range of motion of knee joint extension and flexion were used to evaluate the knee joint function before and after operation in the two groups. The quality of life of the two groups was evaluated by the concise health survey scale. The results showed that 50% of deep venous thrombosis occurred on the first day and 30% on the second day after operation. There was no significant difference in preoperative Lysholm score, HSS score, and knee flexion activity between the observation group and the control group (P > 0.01 ). After 1-month, 5-month, and 1-year follow-up, the effective rate of knee function recovery in the observation group was significantly better than that in the control group. Lysholm score, HSS score, and knee extension and flexion activity were significantly different from those in the control group (P < 0.01 ). The postoperative SF-36 quality of life score of the observation group was significantly higher than that of the control group, indicating that the quality of life of the observation group was significantly better than that of the control group. Therefore, early postoperative rehabilitation training guidance based on automatic extraction algorithm can improve local blood circulation and improve knee function and reduce pain, so as to promote the early recovery of patients.